The size and structure of arm movement variability decreased with work pace in a standardised repetitive precision task - Srinivasan, D.; Samani, A.; Mathiassen, Svend; Madeleine, P. (Taylor & Francis, 2015)
© 2014 Taylor & Francis. Increased movement variability has been suggested to reduce the risk of developing musculoskeletal disorders caused by repetitive work. This study investigated the effects of work pace on arm movement variability in a standardised repetitive pipetting task performed by 35 healthy women. During pipetting at slow and fast paces differing by 15%, movements of arm, hand and pipette were tracked in 3D, and used to derive shoulder and elbow joint angles. The size of cycle-to-cycle motor variability was quantified using standard deviations of several kinematics properties, while the structure of variability was quantified using indices of sample entropy and recurrence quantification analysis. When pace increased, both the size and structure of motor variability in the shoulder and elbow decreased. These results suggest that motor variability drops when repetitive movements are performed at increased paces, which may in the long run lead to undesirable outcomes such as muscle fatigue or overuse.